2017
DOI: 10.1007/s00248-017-1106-8
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent Catalysis of Chlorovirus Population Growth by A Messy Feeding Predator

Abstract: Many chloroviruses replicate in endosymbiotic zoochlorellae that are protected from infection by their symbiotic host. To reach the high virus concentrations that often occur in natural systems, a mechanism is needed to release zoochlorellae from their hosts. We demonstrate that the ciliate predator Didinium nasutum foraging on zoochlorellae-bearing Paramecium bursaria can release live zoochlorellae from the ruptured prey cell that can then be infected by chloroviruses. The catalysis process is very effective,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…First, we determined that chlorovirus-infected cells could influence the movement behavior of P. bursaria. In these experiments, we used the paramecium-free zoochlorellae that are susceptible to the Chlorovirus Osy-NE-ZA1 (5,6). We estimated that Osy-NE-ZA1 infection kinetics are similar to that of the type member of the genus FIG 1 Experimental scheme for evaluating potential of chemotaxis agents associated with chloroviruses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we determined that chlorovirus-infected cells could influence the movement behavior of P. bursaria. In these experiments, we used the paramecium-free zoochlorellae that are susceptible to the Chlorovirus Osy-NE-ZA1 (5,6). We estimated that Osy-NE-ZA1 infection kinetics are similar to that of the type member of the genus FIG 1 Experimental scheme for evaluating potential of chemotaxis agents associated with chloroviruses.…”
Section: Resultsmentioning
confidence: 99%
“…Messy feeding by Didinium spp. releases algal cells into the water column, where they are infected (6). These catalytic processes can contribute to cycles of chlorovirus expansion in temperate lakes (see, e.g., reference 7).…”
mentioning
confidence: 99%
“…This inspired questions about their resistance to degradation as well as how viruses and hosts make contact with one another. Predatory activity on Paramecium bursaria catalyzes this contact by making the endosymbiotic algae available to Chlorella viruses in the environment [ 177 , 178 ]. Another group has shown that Chlorella viruses are more resistant to environmental degradation than other algal viruses, and can even overwinter under ice [ 179 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge this was the first examination of RNA silencing genes in algae beyond core proteins, and the first analysis of their transcription during virus infection. Another aquatic predator, Didinium nasutum, especially the smaller ones, that feed on P. bursaria can rupture the protist by tearing it apart, which also releases the zoochlorellae [230]. This process, which is referred to as "messy feeding", also leads to rapid chlorovirus amplification.…”
Section: Resistance To Chlorovirus Infectionsmentioning
confidence: 99%